2001
DOI: 10.1034/j.1399-6576.2001.045003294.x
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional hypotension from lidocaine infiltration during orthognathic surgery and general anaesthesia

Abstract: Lidocaine induced dose-dependent arterial hypotension when combined with a defined level of general anaesthesia. The causative mechanism is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
14
1
1
Order By: Relevance
“…Enlund et al have reported lidocaine combined with epinephrine might induce dose‐dependent hypotension when combined with a defined level of general anesthesia, but they attributed the reason to the effect of lidocaine (10). However, we believe the infiltration of low‐dose epinephrine elicits hypotension, which was also reported by Anderhuber et al (11) during FESS.…”
Section: Discussionmentioning
confidence: 99%
“…Enlund et al have reported lidocaine combined with epinephrine might induce dose‐dependent hypotension when combined with a defined level of general anesthesia, but they attributed the reason to the effect of lidocaine (10). However, we believe the infiltration of low‐dose epinephrine elicits hypotension, which was also reported by Anderhuber et al (11) during FESS.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthetics are known to produce vasodilation in concentrations used clinically by their direct effect on the smooth muscles of vessel walls, with cocaine being the only exception 15,16 . Enlund et al 17 have reported that lidocaine may induce dose‐dependent arterial hypotension when combined with a defined level of general anesthesia. However, only 40 mg lignocaine was used in our study, and it affected BP only to a small degree.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with higher doses of lidocaine and epinephrine, we also noted unintentional hypotension after submucosal infiltration in conjunction with deep general anesthesia (2). However, the blood pressure reaction was less pronounced, and our conclusion was that the hypotensive reaction was due to lidocaine.…”
Section: Doses Of Lidocaine and Epinephrine And The Following Blood mentioning
confidence: 48%